Pro-tumoral functions of tumor-associated macrophage EV-miRNA. (November 2022) - Cocks, Alexander; Del Vecchio, Filippo; Martinez-Rodriguez, Verena; Schukking, Monique; Fabbri, Muller
Abstract: MicroRNAs (miRNAs) are central players in cancer biology. Their relevance in cancer development, progression and resistance to therapy has been further emphasized by the discovery that they are important cargo component of extracellular vesicles (EVs), which represent a prominent means of inter-cellular communication within the tumor microenvironment (TME). This review article focuses on the interaction between cancer cells and tumor-associated macrophages (TAMs) and in particular on the pro-tumoral phenotype elicited by EV-contained miRNAs released by TAMs and transferred to cancer cells. All main hallmarks of the malignant phenotype are affected by TAM-derived vesicular miRNAs, paving the road to the identification of such miRNAs as promising upcoming novel anti-cancer agents.